O uso da “paródia” nas práticas de leitura: uma análise a partir do olhar dos alunos do 3º ano (1º ciclo) de uma escola pública de Castanhal (PA) - MENDONÇA, Maria Luiza da Silva (2020)
The work has as its theme "The Use of" Parody "in Reading Practices: an analysis from the view of the 3rd year students (1st Cycle) of a public school in Castanhal (PA)". It was chosen as a general objective: to analyze, based on the discourse of the 3rd year students (1st Cycle), how they evaluate the use of the parody textual genre as a pedagogical instrument in the teaching and learning process of reading. As specific objectives: To discuss the contributions of the relationship between playfulness and reading through parody; Highlight the meanings attributed by the students to the use of parody as a pedagogical tool; and, Identify the contributions of parody use to the development of reading. It is problematic because a considerable part of the population has difficulty in getting books or entering a library, even if it is called "public" to read, because of several factors they do not like to read, they have not been encouraged to be true readers, which interferes with the learning process, causing problems or serious learning difficulties in school life, in relation to reading learning. The research is justified, therefore, the Textual Genres are strong allies in the search of the reading with critical knowledge, quality, enthusiasm, joy, humor and satisfaction. The research was bibliographical, field and qualitative in nature, where the data were obtained through the technique of structured interview, with the support of a script. The authors used different materials for theoretical studies: Aragão (1980), Dell'isola (2007), Ferreiro (2004), Freire (2007), Kishimoto (2011), Kleiman (2002), Marcuschi 2008), Santa'anna (2007), Solé (2008), Teberosky (2010), Vygotsky (1998). The results of the research in the students' speech point out that the use of the parody genre in classes is very important, and the contribution is odd, because it develops curiosity, and tends to be a source of stimulus for textual production. And in producing the parody genre, students realize that the Portuguese language is not based on rigid or closed constructions, but that with it, one can create, learn and have fun.